2011
DOI: 10.3109/09286586.2010.545932
|View full text |Cite
|
Sign up to set email alerts
|

Results of a Rapid Assessment of Avoidable Blindness (RAAB) in Eritrea

Abstract: The prevalence of blindness was high compared to recent surveys in Africa. Visual outcome after cataract surgery potentially could be improved by more detailed pre-operative examination, coaching of surgeons, and provision of adequate optical correction, including routine monitoring of visual outcome after cataract surgery. The development of intervention programs for refractive error and glaucoma should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 5 publications
0
28
1
Order By: Relevance
“…14 Most studies (9/11) reported some cases of SVI due to URE, with the highest estimate 0.48% (14.6% of SVI) in Eritrea 11. The proportion of moderate VI due to URE was markedly higher in all studies although there was considerable heterogeneity among studies.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…14 Most studies (9/11) reported some cases of SVI due to URE, with the highest estimate 0.48% (14.6% of SVI) in Eritrea 11. The proportion of moderate VI due to URE was markedly higher in all studies although there was considerable heterogeneity among studies.…”
Section: Resultsmentioning
confidence: 95%
“…The highest prevalence was 0.16% (95% CI 0.13 to 0.18) in Eritrea11 and many surveys found no one blind from URE. Similarly, the prevalence of SVI and VI due to URE in the published studies, ranging from 0 to 0.48% and from 0.66 to 5.71% respectively, is also lower than WHO estimate of 5.95% for the two together.…”
Section: Discussionmentioning
confidence: 99%
“…The only other country contributing two separate published studies was Tanzania, including RAAB surveys from Kilimanjaro and Zanzibar 20 21. Additional RAAB surveys were performed in Botswana,9 Burundi,22 Malawi,17 Rwanda,19 Eritrea12 and Kenya 16. Five studies were national surveys 9 12–14 18.…”
Section: Resultsmentioning
confidence: 99%
“…Data from five studies in South America (Brazil,[25] Chile,[24] Guatemala,[11] Mexico,[24] and Venezuela[24]), six studies in Africa (Botswana,[18] Eritrea,[10] Kenya,[21] Malawi,[6] Rwanda,[7] and Tanzania[9]), and four in Asia (China,[2] India,[3] Iran,[29] and Nepal[1]) were used [Fig. 1].…”
Section: Resultsmentioning
confidence: 99%